UPAYA MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI LARUTAN ASAM, BASA DAN GARAM MELALUI PENERAPAN STRATEGI PEMBELAJARAN RESOURSCE BASED LEARNING (RBL) PADA SISWA KELAS XI IPA 3 DI SMAN 22 BANDUNG - Hasanah Hasanah (UIN AR-RANIRY, 2019)
This research was conducted to improve student learning outcomes using the Resource Based Learning (RBL) strategy. The research method was class action research. The process of this research was carried out through 2 cycles. The researcher used worksheets and evaluation sheets to find out the increase in students' understanding in the upper, middle and lower groups. The subjects in this study were students of class XI IPA 3. The average value of students' abilities in the high group was obtained at 88 in the first cycle and 89 in the second cycle. The medium group average value was 79 in the first cycle and 85 in the second cycle. The low group average value 66 in the first cycle and 72 in the second cycle. Based on learning outcomes data obtained in the first and second cycle, proving that the learning outcomes of class XI IPA 3 students of SMAN 22 Bandung, through the Resource Based Learning (RBL) strategy was increased.